1998
DOI: 10.2486/indhealth.36.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Prison Life Style to Blood Pressure, Serum Lipids and Obesity in Women Prisoners in Japan.

Abstract: This prospective study of female prison inmates assessed the effects of prison labour life style on the blood pressure (BP), serum lipids, and body mass index of pre-and postmenopausal female prisoners. This study was carried out in the largest women's prison, located in a town in the North East of Japan. The prison serves a reasonably large community. Three hundred and twelve premenopausal female prisoners and 88 postmenopausal female prisoners in a women's prison participated in this study. Weight and height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…A total of nine studies were included in the meta‐analysis. The meta‐analysis was conducted with and without the study by Nara and Igarashi because this latter study was conducted in a prison with caloric restriction and obligatory work and physical activity and thus is unlikely to be representative of prisons in many other settings. We reported only mean results excluding the study by Nara and Igarashi.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of nine studies were included in the meta‐analysis. The meta‐analysis was conducted with and without the study by Nara and Igarashi because this latter study was conducted in a prison with caloric restriction and obligatory work and physical activity and thus is unlikely to be representative of prisons in many other settings. We reported only mean results excluding the study by Nara and Igarashi.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were found through a search of grey literature. Therefore, a total of 16 studies were included in this review (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). Figure 1 shows the steps followed in the literature search.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Japanese study, (Nara & Igarashi, 1998) focused on female prisoners also demonstrated improvement in outcomes for blood pressure, total cholesterol, triglycerides, and body mass index (BMI) associated with light activity for a period of 30 minutes. These findings were even more significant among pre-menopausal women.…”
Section: Cvd Risk Factors Awareness and Lifestyle Interventions Amongmentioning
confidence: 95%